Learning and motivation associated with changes in the lives and practices of architects: A study in support of a natural learning model for professionals - Michael A. Price; Evelyn Knowles (Adult Education Research Conference, 1995)
Findings from a study of change among architects support the broader application of Fox’s model of learning and changing. This model describes professionals’ natural learning process within the context of change and provides a framework for research in learning, motivation, and change.